Psychophysiological stress in judo athletes during competitions - Filaire, E.; Sagnol, M.; Ferrand, C.; Maso, F.; Lac, G. (The Journal of Sports Medicine and Physical Fitness, 2001)
The relationships between psychophysiological variables were investigated by comparing physiological responses (salivary cortisol and testosterone concentrations) and psychological responses (measured by the Competitive State Anxiety Inventory-2 -CSAI-2-and by the State-Trait Anxiety Inventory -STAY-) prior to judo competitions at two levels (regional versus interregional). METHODS: Twelve male judo competitors at interregional level (mean age 22.2+/-1.6 years) entered the experimentation after informed consent. Judo athletes completed the CSAI-2 prior to both competitions and collected saliva for cortisol and testosterone analysis on three occasions: during a resting day (baseline values) and prior to and after both competitions. Trait scales of the STAI (Y-2) were used during a resting baseline period with no stressful situations in order to measure participant's self reported anxiety. RESULTS: Cognitive and somatic anxiety were higher in interregional championships compared to regional championships whereas self-confidence was significantly lower. Cortisol levels increased sharply (about 2.5 fold resting levels) throughout both competitions with no changes in testosterone levels. Positive relationships between anxiety components (somatic and cognitive anxiety) and cortisol were noted in both competitions. CONCLUSIONS: Salivary cortisol, together with anxiety components, may provide a better sensitive index of physiological stress than testosterone concentrations.